2012
DOI: 10.1115/1.4005775
|View full text |Cite
|
Sign up to set email alerts
|

Performance Optimization of Abrasive Fluid Jet for Completion and Stimulation of Oil and Gas Wells

Abstract: This paper provides an ovei-view ofthe development and optimization of abrasive-slurryjet methods for completion and stimulation applications. Abrasive particles added to the fluid dramatically reduced the system pressure requirements. The paper discusses the technical capabilities of cutting through various materials and formations and also discusses improvements and proven applications. Abrasive fluid-jet systems are capable of cutting through rocks of all types, and with greater location control that is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…p\ In ----b S rw (11) From Eq. (11), we can determine the maximum injection rate that we can use during the treatment, if the maximum injection rate obtained from Eq.…”
Section: \Hf4>fk(gfrdf -P T )mentioning
confidence: 98%
“…p\ In ----b S rw (11) From Eq. (11), we can determine the maximum injection rate that we can use during the treatment, if the maximum injection rate obtained from Eq.…”
Section: \Hf4>fk(gfrdf -P T )mentioning
confidence: 98%
“…Comparing performance of abrasive water jets injected with xanthan, polyacrylamide (MF-55), and carboxymethylcellulose (CMC) revealed that the incorporation of xanthan resulted in better suspensions, followed by CMC and MF-55. [65][66][67] Also, using xanthan and MF-55 proved beneficial in submerged conditions as it increased the jet-length by 2-3 fold.…”
Section: Xanthanmentioning
confidence: 99%
“…Their performance is below PAM and xanthan additives for a given concentration. 63,67 Non-Newtonian additives Glycerine is a polyol compound, having good tribological properties. 92 Ramanathan compared performance of 10% of glycerine and acrylamide in water as carrier-fluids, to analyze effect of inlet pressure on wall shear and exit kinetic-energy in both cases using CFD analysis.…”
Section: Carboxymethylcellulosementioning
confidence: 99%
“…The polymers are long-chained molecules that impart a viscoelastic fluid behaviour to the suspension mixture. There are various polymer additives during the Suspension-type AWJ machining of several materials, including SUPER-WATER/polyacrylamide (PAM) [15][16][17], Xanthan [16,18], polyox [19], carboxy methyl cellulose (CMC/ cellulose gum) [16,17] and others. Recently, Wang et al [20] studied the rheological properties of the suspension mixture with PAM and CMC used in suspension-type AWJs.…”
Section: Introductionmentioning
confidence: 99%